The global anaerobic regulator Anr, is involved in cell attachment and aggregation influencing the first stages of biofilm development in Pseudomonas extremaustralis - Tribelli, Paula Maria; Hay, Anthony; Lopez, Nancy Irene (PLoS ONE)
Pseudomonas extremaustralis is a versatile Antarctic bacterium, able to grow under microaerobic and anaerobic conditions and is related to several non-pathogenic Pseudomonads. Here we report on the role of the global anaerobic regulator Anr, in the early steps of P. extremaustralis biofilm development. We found that the anr mutant was reduced in its ability to attach, to form aggregates and to display twitching motility but presented higher swimming motility than the wild type. In addition, microscopy revealed that the wild type biofilm contained more biomass and was thicker, but were less rough than that of the anr mutant. In silico analysis of the P. extremaustralis genome for Anr-like binding sites led to the identification of two biofilm-related genes as potential targets of this regulator. When measured using Quantitative Real Time PCR, we found that the anr mutant expressed lower levels of pilG , which encodes a component of Type IV pili and has been previously implicated in cellular adhesion. Levels of morA, involved in signal transduction and flagella development, were also lower in the mutant. Our data suggest that under low oxygen conditions, such as those encountered in biofilms, Anr differentially regulates aggregation and motility thus affecting the first stages of biofilm formation. Fil: Tribelli, Paula Maria. Consejo Nacional de Invest.cientif.y Tecnicas. Oficina de Coordinacion Administrativa Ciudad Universitaria. Instituto de Quimica Biologica de la Facultad de Cs. Exactas y Naturales; Fil: Hay, Anthony. Fil: Lopez, Nancy Irene. Consejo Nacional de Invest.cientif.y Tecnicas. Oficina de Coordinacion Administrativa Ciudad Universitaria. Instituto de Quimica Biologica de la Facultad de Cs. Exactas y Naturales;